Tumor suppressor genes: VOL.2 - El-Deiry, Wafik S; Ed (Methods in molecular biology (Clifton, N.J.), v. 223., 2003)
It has become clear that tumors result from excessive cell proliferation and a corresponding reduction in cell death caused by the successive accumulation of mutations in key regulatory target genes over time.